Comprehensive Measures of GDP and the Unrecorded Economy - Shrestha, Manik (IMF Working Papers; Working Paper, 2000)
Comprehensive coverage of national accounts estimates is important; however, it is often thwarted by gaps in the recording of economic activity - the so-called 'unrecorded economy'. This paper sets out pragmatic statistical approaches for incorporating the unrecorded economy in the national accounts. It describes sources and methods to capture the unrecorded economy and discusses specific issues that arise from the use of indirect sources and techniques. Furthermore, the paper elaborates approaches for collecting data on the unrecorded economy, particularly on economic activities of the household sector.